Extraction of 3D Displacement of Mining Area Surface Based on Multi-Source Data Fusion - Han, Jiankun (International Journal of Natural Resources and Environmental Studies, 2025)
Large-scale, continuous, and high-intensity mining of underground coal resources in mining areas often leads to large-scale surface subsidence, sometimes up to several meters. The use of InSAR to monitor subsidence usually faces two key challenges: rapid and large-gradient subsidence often leads to image decorrelation, which hinders the acquisition of accurate deformation measurements. In addition, InSAR-based monitoring is limited to one-dimensional line-of-sight (LOS) displacement, which limits its ability to fully capture three-dimensional surface deformation. To overcome these obstacles, this study combines InSAR and PIM technology, and uses a spatial interpolation method to obtain continuous surface subsidence data in a geographic coordinate system to generate a surface displacement basin map in the mining area. A three-dimensional displacement model was established based on the proportional relationship between horizontal surface movement caused by mining of inclined coal seams and surface inclination. A field test was carried out in Yangchangwan Coal Mine, and the method was applied and its accuracy analyzed using five Sentinel-1A images from October 2022 to January 2023, combined with leveling data. The experimental results show that this method can obtain surface subsidence information around the mining area more accurately, the overall subsidence situation is more consistent with the actual situation, and the monitoring capability is significantly improved compared with InSAR and PIM.